Extraction of Gallic Acid and Ferulic Acid for Application in Hair Supplements - Pedro Velho; Catarina S. Rebelo; Eugénia A. Macedo (Molecules, 2023)
Food supplements based on antioxidants and vitamins are often prescribed to correct inefficiencies in the human diet and delay diseases such as premature aging and alopecia (temporary or permanent hair loss), given the free radical scavenging activity of these biomolecules. By reducing the concentration of reactive oxygen species (ROS), which promote abnormal hair follicle cycling and morphology, follicle inflammation and oxidative stress are reduced, minimising the effects of these health issues. Gallic acid (GA), which is significantly present in gallnuts and in pomegranate root bark, and ferulic acid (FA), commonly found in brown rice and coffee seeds, are very important antioxidants for the preservation of hair colour, strength and growth. In this work, these two secondary phenolic metabolites were successfully extracted in the Aqueous Two-Phase Systems (ATPS) {ethyl lactate (1) + trisodium citrate (2) + water (3)} and {ethyl lactate (1) + tripotassium citrate (2) + water (3)} at 298.15 K and 0.1 MPa, moving towards the application of these ternary systems in extracting antioxidants from biowaste and their a posteriori processing as food supplements for hair fortification. The studied ATPS provided biocompatible and sustainable media for the extraction of gallic acid and ferulic acid, yielding low mass losses (<3%) and contributing to an eco-friendlier production of therapeutics. The most promising results were obtained for ferulic acid, which attained maximum partition coefficients (K) of 15 <semantics>±</semantics> 5 and (3 <semantics>±</semantics> 2) · 101 and maximum extraction efficiencies (E) of (92.7 <semantics>±</semantics> 0.4)% and (96.7 <semantics>±</semantics> 0.4)% for the longest tie-lines (TLL = 69.68 and 77.66 m%) in {ethyl lactate (1) + trisodium citrate (2) + water (3)} and {ethyl lactate (1) + tripotassium citrate (2) + water (3)}, respectively. Moreover, the effect of pH on the UV-Vis absorbance spectra was studied for all the biomolecules to minimise errors in solute quantification. Both GA and FA were found to be stable at the used extractive conditions.